The difference of affect improvement effect of music intervention in aerobic exercise at different time periods - Lu, Li; Tao, Meng; Gao, Jingchuan; Gao, Mengru; Zhu, Houwei; He, Xiaolong (Frontiers in Physiology, 2024)
Objectives: A randomized controlled experimental design that combines exercise and music intervention was adopted in this study to verify whether this approach could help improve human affect. The differences in the effect of music listening on affective improvement were compared in four different periods: before, during, and after aerobic power cycling exercise and the whole exercise course. Method: total of 140 subjects aged 19-30 years were recruited and randomly divided into four music intervention groups, namely, the pre-exercise, during-exercise, post-exercise, and the whole-course groups. The subjects' demographic and sociological variables and daily physical activities were collected using questionnaires. Individual factors, such as the subjects' noise sensitivity, personality traits, and degree of learning burnout, were collected via scale scoring. A laboratory in Zhejiang Normal University was selected as the experimental site. The four subject groups wore headphones and completed 20 minutes of aerobic cycling (i.e., 7 minutes of moderate-intensity cycling + 6 minutes of low-intensity interval cycling+ 7 minutes of moderate-intensity cycling after returning to a calm state (no less than 20 minutes) for post-testing. The affect improvement indicators (dependent variables) collected in the field included blood pressure (BP), positive/negative affect, and heart rate variability indicators (RMSSD, SDNN, and LF/HF). Results: (1) Significant differences were found in the participants' systolic BP (SBP) indices and the effect of improvement of the positive affect during the exercise-music intervention among the four groups at different durations for the same exercise intensity. (2) Music intervention for individuals during exercise contribute more to the reduction of SBP than the other three time periods. Improvement in the participants' negativity affective score was also better during exercise, and it was significantly different than the other three time periods . No significant differences were found in the improvement effects of the other effective indicators for the four periods. Conclusions: Exercise combined with music intervention has a facilitative effect on human affect improvement, and listening to music during exercise has a better impact on affective improvement than music interventions at the other periods. When people perform physical activities, listening to music during exercise positively affects the progress effect among them.